Muscle function deterioration in patients with haemophilia: Prospective experience from Costa Rica. Issue 4 (26th March 2018) - Seuser, A.; Navarrete‐Duran, M.; Auerswald, G.; Mancuso, M. E.
Abstract : Introduction: In haemophilia, recurrent joint bleeds are responsible for the development of chronic joint damage, because blood induces biochemical changes in joint structures. Joint degeneration is a long process, and structural damage is often preceded by joint dysfunction, which is represented by quantitative and qualitative changes in the contraction pattern of muscles around the joints. Muscle function in patients with haemophilia is still poorly investigated. Aim: The aim of this 2‐year prospective study was to assess the changes in muscle function of lower limbs in a group of patients affected with haemophilia in San José, Costa Rica. Methods: Muscle function of lower limbs was assessed by means of surface electromyography (sEMG) accomplished at study enrolment and after 2 years of follow‐up. Gluteus medius, vastus medialis, biceps femoris, gastrocnemius and tibialis anterior were examined. All patients underwent concurrent clinical examination using Haemophilia Joint Health Score (HJHS). Results: Sixty patients aged 2‐43 years with severe haemophilia underwent clinical and sEMG evaluation. Thirty‐two patients (53%) had target joints. sEMG parameters were altered in all patients and were not correlated to the presence of target joints and/or an abnormal HJHS. Muscle function deterioration was observed after 2 years of follow‐up despite an unmodified HJHS. Conclusions: Muscle function of lower limbs as detected by means of sEMG was impaired in patients with haemophilia irrespective of the presence of overt joint damage. sEMG is a simple and sensitive assessment tool able to detect muscle dysfunction and so favouring the implementation of early rehabilitation therapy.